Market Orientation and Organizational Performance from the Resource Advantage Theory of Competition Perspective - Norizan, Remli; Wan Norhayate, Wan Daud; Fakhrul Anwar, Zainol (2013)
The purpose of this paper is to consider how resource-advantage theory of competition can be used to explain the role of market orientation and innovation in achieving superior performance within the organization. A number of authors have explored the applicability of this theory. This paper is based on the research conducted among the Composite Takaful Operators in Malaysia. The research framework was analyzed from the perspective of resource- advantage theory of competition.